Mappatammaq Mangaji in Mandar, West Sulawesi: Childrearing Patterns Based on the Qur'an in the Anthropological Perspective of Islamic Law - Nurdin, Abidin; Baharuddin, Elviana; Sumardi, Dedy; L, Idrus; Mutiawati, Ida (El-Usrah: Jurnal Hukum Keluarga, 2024)
This study aims to discuss the Mappammaq Mangaji tradition in Mandar, West Sulawesi in relation to al-Quran-based child rearing patterns from an Islamic legal anthropological perspective. Mappatammaq mangaji is a tradition carried out by the community when someone is able to read the Koran fluently. This study is an empirical legal study with an anthropological approach to Islamic law as an analytical tool. Data was collected based on in-depth interviews and literature studies. This study concludes that the mappatamaq mangaji tradition carried out by the Mandar community in West Sulawesi is an acculturation of Islamic teachings and cultural values. Mappatammaq mangaji, including sayyeang pattuqduq (dancing horse), kalindaqdaq(Mandar poetry) and mabbaranji. When viewed from a legal anthropology perspective, the mappammaq mangaji tradition in Mandar society is an integration and acculturation between Islamic law and local traditions. This local tradition has become a living law and continues to be practiced in the culture of the Mandar people. So it can be said that if Islamic law is practiced in society and has become a culture, it will continue to survive today and in the future, because Islamic law has a cultural space. If it is related to the objectives of Islamic law, especially benefit, then this provides benefits, especially in the context of child rearing patterns based on the Qur’an, so that children receive care and education from parents and families based on the values of the Qur’an.